THE ISOTOPE GEOCHEMISTRY AND COSMOCHEMISTRY OF MAGNESIUM - Young E.D.; Galy A. (My University, 2004)
Magnesium is second only to oxygen in abundance among the rock-forming elements and is an important element in the oceans and in hydrological and biological systems. Differences in the relative abundances of its three stable isotopes, 24Mg (78.99%), 25Mg (10.00%), and 26Mg (11.01%), are expected as a result of physicochemical processes because of the large relative mass differences of 4 and 8% between 25Mg and 26Mg, and 24Mg, respectively. Although isotopes of Mg have been used for many years as tracers in artificially spiked systems (in which the abundance of one isotope is enriched) (Cary et al. 1990; Dombovari et al. 2000), reliable measurements of 25Mg/24Mg and 26Mg/24Mg in natural systems have been limited historically by the 1‰ (one part per thousand) reproducibility imparted by instrumental mass fractionation effects. In order to be useful for many geochemical and cosmochemical applications the isotope ratios of Mg must be resolved to ≤ 200 parts per million (ppm). As a result, with a few exceptions (e.g., Davis et al. 1990; Goswami et al. 1994; Russell et al. 1998), many past studies of Mg isotope ratios focused on detection of non-mass dependent, so-called “anomalous” Mg isotopic effects rather than on investigations of mass-dependent fractionation. The principle outcome of this focus was the discovery of radiogenic 26Mg (26Mg*) in primitive meteorites (Gray and Compston 1974; Lee and Papanastassiou 1974).